Aktivitas Anti Dislipidemia Ekstrak Etil Asetat Rimpang Temu Mangga (Curcuma mangga Valeton and Zijp): Antidyslipidemic Activity of Ethyl Acetate Extract of Temu Mangga Rhizome (Curcuma mangga Valeton and Zijp) - Dyan Fitri Nugraha; Kunti Nastiti; Rahmayani Rahmayani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Statins are first-line drugs that are often used in the treatment of cardiovascular disease. It is noted that statins have various side effects, such as myalgia, rhabdomyolysis, and are considered to trigger diabetes mellitus. Meanwhile, the use of natural ingredients such as the rhizome of Intersection mango (Curcuma mango Valeton and Zijp) is often used empirically by the community in the treatment of dyslipidemia. The purpose of this study was to determine the effectiveness of anti-dyslipidemia and the dose of ethyl acetate extract of the temu mango rhizome which was effective as anti-dyslipidemia. This research method is a true experimental design with a pre-post test with control group on test animals with 5 test groups induced by cooking oil for 14 days, then given treatment for 14 days. Measurement of total cholesterol, triglyceride, LDL, and HDL parameters as well as body weight of test animals as additional parameters. The test group was divided into 3 doses, namely 90 mg, 180 mg, and 360 mg per 200 grams of test animals. The results showed that there was no significant difference between the extract groups, both in lipid profile and body weight of the test animals. However, a dose of 360 mg had the best activity, being able to lower cholesterol, triglycerides, and LDL, but was able to increase HDL levels.